A Test of the Relationship Between Political Connection and Indirect Costs of Financial Distress in Indonesia - Wijantini (Asian Academy of Management Journal of Accounting and Finance, 2007)
This study finds that political connection affects indirect costs of financial distress in Indonesia. It applies changes of industry-adjusted operating profit and annualized changes of industry-adjusted sales as proxies of the costs. Evidence from 1997–2002 indicates that Indonesian firms with political connections lower their indirect costs of financial distress. Specifically, these results hold for the costs estimated as changes of industry sales after controlling for firm size, leverage, portion and complexity of bank loan. Also, there is significant difference in level of indirect costs of financial distress between politically connected and non-politically connected firms. The findings suggest that being politically connected provide significant benefits for financially distressed firms.